2014
DOI: 10.1016/j.febslet.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Tracking bacterial pathogens with genetically‐encoded reporters

Abstract: During the infectious process, bacterial pathogens are subject to changes in environmental conditions such as nutrient availability, immune response challenges, bacterial density and physical contacts with targeted host cells. These conditions occur in the colonized organs, in diverse regions within infected tissues or even at the subcellular level for intracellular pathogens. Integration of environmental cues leads to measurable biological responses in the bacterium required for adaptation. Recent progress in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 100 publications
1
24
0
Order By: Relevance
“…Despite these recent advances in molecular tools, there is a need for improved in vivo analysis of bacterial pathogens (9). It is necessary to validate the expression of individual genes identified by next-generation sequencing applications, such as transposon insertion sequencing (Tn-seq) (10), or to complement in vivospecific genetic techniques, such as in vivo expression technology (IVET) (11).…”
mentioning
confidence: 99%
“…Despite these recent advances in molecular tools, there is a need for improved in vivo analysis of bacterial pathogens (9). It is necessary to validate the expression of individual genes identified by next-generation sequencing applications, such as transposon insertion sequencing (Tn-seq) (10), or to complement in vivospecific genetic techniques, such as in vivo expression technology (IVET) (11).…”
mentioning
confidence: 99%
“…Biologically speaking, this environment is essential for the full understanding of a given pathogen's invasive strategies and the complex host response; however, this also places additional complexity and limitations in regards to imaging, particularly in maintaining cellular and molecular resolution. Novel tools and studies addressing bacterial infection in vivo are frequently reported in the literature (4,5). However, emphasis has been traditionally placed on qualitative observations at the expense of extensive quantitative efforts.…”
mentioning
confidence: 99%
“…Single-cell RNA-seq is useful to detect cell-to-cell variability in non-coding RNA expression. Physiology of intracellular bacteria located in defined subcellular locations can be also monitored with reporters based on fluorescent proteins expressed constitutively or promoters responding to the infection (Campbell-Valois and Sansonetti, 2014). Transcriptome and proteome quantification with single-molecule sensitivity was performed in single E. coli cells (Taniguchi et al, 2010).…”
Section: Isolating Intracellular Bacteria From Eukaryotic Cellsmentioning
confidence: 99%